2020
DOI: 10.1177/0036850420959876
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic-empirical evaluation of specific polymer-modified asphalt binders effect on the rheological performance

Abstract: Major distresses such as rutting, fatigue, and thermal cracking are facing asphalt pavement structures due to continuous heavy traffic loading and climate change. The modification of asphalt binders (one of the main components of the asphalt paving mix) has the potential to mitigate distresses through using different additives. Polymer modified asphalt (PMA) binders showed a noticeable resistance to pavement distresses as reported in previous studies. The present study aims to evaluate the effect of polymer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…To account for the cumulative effects of distresses such cracking, rutting, faulting, and punchouts on the loss of pavement smoothness during the whole design period, IRI is computed incrementally in MEPDG [27][28][29].…”
Section: Effect Of Modifier On International Roughness Index (Iri)mentioning
confidence: 99%
“…To account for the cumulative effects of distresses such cracking, rutting, faulting, and punchouts on the loss of pavement smoothness during the whole design period, IRI is computed incrementally in MEPDG [27][28][29].…”
Section: Effect Of Modifier On International Roughness Index (Iri)mentioning
confidence: 99%
“…As a result, these variables deteriorate the performance of the structure and, by extension, the asphalt surface layer over time. Asphalt mixture design incorporates numerous factors that influence the performance of the resultant mixes, including mineral aggregates, asphalt binder content, and air content [2]. Therefore, a great deal of care must be taken in the preparation and selection of the mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of modifiers have been tested by researchers to mitigate the distress associated with the behavior of conventional asphalt binders [1][2][3][4]. Many researchers concluded that the asphalt binder modification increased the complex modulus of bitumen at high temperatures while reducing it at low temperatures [5][6][7][8][9]. Also, the bitumen modifier shows high resistance to thermal cracking, rutting, and…”
mentioning
confidence: 99%